ANALISA YURIDIS PERKAWINAN BEDA AGAMA DALAM PERSPEKTIF HUKUM POSITIF DI KOTA SURABAYA - Indri Dwi Cahyani; Adi Suliantoro (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2023)
Interreligious marriage has remained a controversial topic in society since the time of Marriage Law No. 1 of 1974. The agreements and rules governing interfaith marriages are primarily aimed at whether different marriages are valid. Look only at Law No. 6 of 2006 on Population Control. Couples married to different religions can apply to the district court, but this is limited to registration of marriage only, but what regulates whether it is legal? No regulations yet. The Indonesian Islamic scholar, particularly in his KHI Compilation of Islamic Law, states that interreligious marriages are void, which is supported by his 2005 MUI Fatwa on Interreligious Marriage. In this study, the authors use a prescriptive legal approach. It is a method of studying forensic research conducted on literature or secondary data and using deductive reasoning and coherent truth criteria. Deductive thinking should be understood as a way of thinking that draws conclusions from proven-true generalities and is directed to specifics. Interreligious marriage cannot be justified on the basis of Marriage Law and Summarizing Islamic Law, as the purpose of these rules is to prevent greater harm/loss in addition to the resulting benefit/benefit.